Effect of Changes in Photoperiods on Melatonin Expression and Gut Health Parameters in Laying Ducks - Cui, Yao-ming; Wang, Jing; Zhang, Hai-jun; Qi, Guang-hai; Qiao, Han-zhen; Gan, Li-ping; Wu, Shu-geng (Frontiers in Microbiology, 2022)
We investigated the effect of photoperiod on ileal morphology, barrier function, short chain fatty acids (SCFAs) contents, microbial flora, melatonin expression and synthesis in laying ducks. After adaption, a total of 180 Jinding laying ducks (252 days old) were randomly divided into 3 treatments, receiving 12L (hours of light):12D (hours of darkness), 16L:8D, or 20L:4D, respectively. Each treatment had 6 replicates with 10 birds each. The formal experiment lasted 58 days. Compared with 12L:12D, the significantly higher values of villus height and goblet cell percentage were observed in 16L:8D treatment, accompanied with the higher mRNA relative expression of zonula occludens-1, zonula occludens-2, zonula occludens-3, claudin-1, occludin and mucin 2 (P ˂ 0.05). Besides, significantly higher values of acetate, propionate, butyrate and total SCFAs concentrations were simultaneously observed in ileal chyme of 16L:8D treatment (P ˂ 0.05). As to ileal microbial community, the results of principal coordinate analysis visually presented that 3 photoperiod groups were mainly scattered into 3 clusters, indicating the microbiota composition in different photoperiod treatments were quite dissimilar. The lower values of Shannon indicators were observed 20L:4D treatment (P ˂ 0.05), meaning the microbiota α-diversity decreased in 20-h photoperiod. The relative abundance of Actinobacteria, Fusobacteria and Proteobacteria at phylum level, Fusobaterium, Clostridium_sensu_stricto_1, and Pectobacterium at genus level kept a propriate balance in 16L:8D photoperiod. Melatonin level in serum decreased with the increasing photoperiods at 6:00 and 12:00, which was consistent with melatonin receptors expressions in hypothalamus and ileum tissue. Meanwhile, the adenosine 3’,5’ cyclic phosphate (cAMP) contents were significantly down-regulated in pineal gland (P ˂ 0.05), in response to the increase in photoperiod. To sum up, an appropriate photoperiod could improve ileal morphology, barrier function, SCFAs profile and microbial flora, which may be attributed to the appropriate regulation of circadian rhythm through melatonin as well as its receptors expression, and 16 h could be an adequate photoperiod for laying ducks.